Utilization of Blended Learning Strategies Combined With Content Area Literacy to Improve The Capabilities of Writing Scientific Works at University - Muhammad Hambali; Novi Eka Susilowati (Jurusan Sastra Indonesia, 2017)
The facts show that the culture of students' literacy, including the culture of writing scientific papers, is low. Therefore, it is necessary to improve the culture of student literacy. One of them is by utilizing blended learning strategy combined with content area literacy to improve the ability to write scientific papers. This blended learning strategy allows students to read, write, and develop critical thinking combined with the use of communication and information technology that is characteristic of activity in the current era of technology. A blended learning strategy is done by assigning students to write scientific papers, while the content area literacy is done by deepening the substantive aspects of the topic of written scientific papers. When the course of writing scientific papers took place, students follow lectures face to face and combined with learning face-to-face (virtual learning). This learning brings advantages such as giving students the opportunity to work and consult scientific papers written anytime and anywhere.